Mandalika Specifics: A Conceptual Analysis of Opportunities and Challenges in Tourism-Based Development Strategy in Indonesia - Lalu Suryadi S; Agus Suman; Marlina Ekawaty; Ferry Prasetyia (Politeknik Siber Cerdika Internasional, 2026)
Background: The development of tourism-based Special Economic Zones is one of the Indonesian government's strategies to drive regional economic growth, attract investment, and reduce development disparities between regions. The Mandalika Special Economic Zone in Lombok, West Nusa Tenggara Province, is a national priority project designed as a new growth center through the integration of investment, infrastructure, and the development of world-class tourism sectors. Objective: This study aims to analyze the strategic rationality of area development, identify opportunities for economic, social, and environmental benefits, and evaluate the challenges of implementing inclusive and sustainable development. Methods: The research uses a qualitative approach with a conceptual design through literature studies and analysis of policy documents relevant to the development of special economic zones and tourism development. The analytical framework integrates the theory of special economic zones, the tourism-led growth hypothesis, and the perspectives of sustainable and inclusive development. Results: The analysis results indicate that the Mandalika SEZ has significant potential to drive regional economic growth through increased investment, job creation, strengthening the service sector, and enhancing national tourism competitiveness. Strategic infrastructure and the hosting of international events have also increased the region's visibility on a global level and created economic multiplier effects for supporting sectors, including micro, small, and medium enterprises. However, this study also identifies various key challenges including land acquisition issues, the inclusiveness of development for local communities, pressure on the carrying capacity of the coastal environment, and the complexity of governance and institutional coordination. The long-term success of the region greatly depends on the ability to integrate economic growth with the principles of environmental sustainability and social justice. Conclusion: Therefore, strengthening governance, participatory planning, developing local community capacity, and implementing sustainable development principles are key factors in ensuring that the Mandalika SEZ not only functions as an international tourist destination but also as an instrument for inclusive and sustainable regional economic transformation.